Home as a Workplace: Demographic Profiles and their Implications to Work-Family Conflict - Sangil, Francis Ion (Journal of Interdisciplinary Perspectives, 2025)
The COVID-19 pandemic profoundly affected businesses, organizations, and educational institutions. Private school employees were compelled to telecommute due to quarantine restrictions, increasing the risk of work-family conflict. This study investigates if demographic variables impact work-to-family and family-to-work conflict levels and explores common challenges telecommuting employees face. The study is under the comparative study design. T-test and frequency distribution were utilized as statistical treatment. The results also indicated significant differences in the levels of family-to-work conflict (p=0.001) between males and females, as well as in work-to-family conflict (p=0.000) and family-to-work conflict (p=0.005) levels between managerial and non-managerial employees. The study also found common challenges employees encounter when working from home, including difficulty maintaining and managing productivity, lack of physical interactions and socialization with co-workers, feelings of loneliness and isolation, and difficulty in getting and staying organized. The research contributes theoretically by examining the concept of work-family conflict, specifically in telecommuting during the COVID-19 pandemic. It builds upon existing theories, such as role theory, to explore how conflicting demands from work and family spheres affect employees working from home. The findings offer valuable insights into human resource management practices. The study suggests that organizations should consider implementing family-friendly HR practices, training and development initiatives, and other programs tailored to address telecommuting challenges and work-family conflict.